2014
DOI: 10.7314/apjcp.2014.15.18.7959
|View full text |Cite
|
Sign up to set email alerts
|

Do Clinical Features and Survival of Single Hormone Receptor Positive Breast Cancers Differ from Double Hormone Receptor Positive Breast Cancers?

Abstract: The significance of the single hormone receptor positive phenotype of breast cancer is still poorly understood. The use of hormone therapy has been found to be less effective for this type, which has a survival outcome midway between double positive and double negative phenotypes. The aim of this study was to investigate differences in patient and tumor characteristics and survival between double-receptor positive (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
7
0
2
Order By: Relevance
“…Ng et al reported that the ER−/PgR+ phenotype had no distinct histopathological characteristics compared to the ER+/PgR+ and ER−/PgR− phenotypes and no prognostic impact [7]. In contrast, Rakha et al reported poorer survival of ER−/PgR+ cases compared with ER+/PgR+ cases [5].…”
Section: Discussionmentioning
confidence: 99%
“…Ng et al reported that the ER−/PgR+ phenotype had no distinct histopathological characteristics compared to the ER+/PgR+ and ER−/PgR− phenotypes and no prognostic impact [7]. In contrast, Rakha et al reported poorer survival of ER−/PgR+ cases compared with ER+/PgR+ cases [5].…”
Section: Discussionmentioning
confidence: 99%
“…Next, the data was clustered based on the receptor status of breast cancer patients identified via immunohistochemistry (IHC). Receptor status was selected to cluster the dataset, mainly because it was used to classify the records obtained from breast cancer patients for further analysis in studies associated to survival prediction [8, 9, 37, 38]. Three clusters were segregated based on Estrogen receptor (ER) status, Progesterone receptor (PR) status, and c-er-b2 status, as listed in Table 3.…”
Section: Methodsmentioning
confidence: 99%
“…Previously clinicians have used basic software programs, such as Microsoft Excel, SPSS, and STATA [79], in analysing factors influencing breast cancer survival rate. These conventional statistical methods are not really adaptable in identifying new variables as well as generating creative and integrative visualisations [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ER (+) BC patients have longer relapse-free survival and overall survival compared to the ER (-) breast carcinomas (Hoch et al, 1999;Zhang et al, 2014). As part of BC treatment, the presence of ER has become an important determinant for predicting the response to adjuvant endocrine therapy with tamoxifen (Dowsett et al, 2008;Ng et al, 2014). However, 30-50% of these cases do not respond to or develop resistance to tamoxifen (Girault et al, 2006).…”
Section: Introductionmentioning
confidence: 99%